2007
DOI: 10.1182/blood-2007-04-086611
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated atherogenesis and neointima formation in heparin cofactor II–deficient mice

Abstract: Heparin cofactor II (HCII) is a plasma protein that inhibits thrombin when bound to dermatan sulfate or heparin. HCIIdeficient mice are viable and fertile but rapidly develop thrombosis of the carotid artery after endothelial injury. We now report the effects of HCII deficiency on atherogenesis and neointima formation. HCII-null or wild-type mice, both on an apolipoprotein E-null background, were fed an atherogenic diet for 12 weeks. HCII-null mice developed plaque areas in the aortic arch approximately 64% la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 37 publications
2
35
0
3
Order By: Relevance
“…All those aberrant phenotype were ameliorated by administration of human purified HCII protein. 48 Vicente et al also reported acceleration of neointimal formation in HCII −/− St Louis mice and HCII +/+ mice 3 weeks after mechanical dilation of the common carotid artery, 49 which is in agreement with our results.…”
Section: Exaggerated Vascular Remodeling In Hcii-deficient Micesupporting
confidence: 83%
See 1 more Smart Citation
“…All those aberrant phenotype were ameliorated by administration of human purified HCII protein. 48 Vicente et al also reported acceleration of neointimal formation in HCII −/− St Louis mice and HCII +/+ mice 3 weeks after mechanical dilation of the common carotid artery, 49 which is in agreement with our results.…”
Section: Exaggerated Vascular Remodeling In Hcii-deficient Micesupporting
confidence: 83%
“…48 Vicente et al also generated HCII −/− (St Louis) ApoE −/− mice and quantified the observed aortic atherosclerosis. 49 Their double mutant mice manifested greater atherosclerotic plaque areas in the aortic arch compared with that generated by the HCII +/+ ApoE −/− mice. 49 …”
Section: Exaggerated Vascular Remodeling In Hcii-deficient Micementioning
confidence: 99%
“…In addition, we and others have recently reported that high plasma HC activity reduced the restenosis of coronary arteries and femoral arteries after stenting 26,45) and attenuated carotid plaque formation 27) in elderly patients. In experimental animal studies using HC -deficient mice, we and Tollefsen's group have shown accelerated vascular remodeling in HC -deficient mice with increased inflammatory cytokines and chemokine gene expression and oxidative stress 29,30) . Taken together, these observations suggest that HC has a pivotal role in protection against "systemic atherosclerosis" in elderly individuals with atherosclerotic risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported an elderly woman with congenital HC deficiency who manifested multiple atherosclerotic disorders 25) , and we have reported the results of clinical studies showing that HC can reduce in-stent restenosis after percutaneous coronary intervention and reduce plaque formation in the carotid artery [26][27][28] . Moreover, we and Tollefsen's group have reported that prominently accelerated vascular remodeling, including atherosclerosis, was observed in HC -deficient mice compared to HC wild-type mice 29,30) . These observations suggested a potential role of HC in counteracting the development of PAD by inhibiting thrombin action in peripheral arteries; however, it is unclear whether HC can contribute to reducing the morbidity of PAD.…”
Section: Introductionmentioning
confidence: 99%
“…As HCII can counteract the actions of thrombin at injured vascular walls, we, and others, have investigated and confirmed the protective role of HCII against atherosclerosis in clinical examinations and studies using HCII-deficient mice. [9][10][11][12][13][14][15] As the development of vascular remodeling, including atherosclerosis, has been shown to be closely associated with cardiac remodeling in humans and experimental animal models, we hypothesized that HCII is involved in the process of not only atherosclerosis, but also cardiac remodeling. In order to clarify this issue, we investigated the relationships between plasma HCII activity and surrogate markers with respect to cardiac remodeling in elderly subjects with cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%